Development and Validation of Stability indicating RP- HPLC method for Simultaneous Estimation of Sofosbuvir and Ledipasvir in Bulk Tablet Dosage Form - Mankar, S.D.; Bhawar, S.B.; Dalavi, P.R. (Journal of Drug Delivery and Therapeutics, 2019)
The present research work describes a simple, accurate, precise, effective, Stability indicating RP-HPLC method for simultaneous estimation of Sofosbuvir and Ledipasvir in their tablet dosage form. A reverse phase high performance chromatographic method was developed for simultaneous estimation of Sofosbuvir and Ledipasvir their combined dosage. The separation was achieved by Inertsil ODS C18 column (150X4.6mm, 5µm) column, and ACN: 0.1% TFA in the proportion of 30:70 %v/v as mobile phase, at a flow rate of 1 ml/min. Detection was carried out at 245 nm.  For RP-HPLC method results of the validation indicate that the method was linear in the range of 100-600μg/ml for Sofosbuvir and 22.5-135μg/ml for Ledipasvir.  The % recoveries for Sofosbuvir and Ledipasvir obtained in the accuracy study were 99.92-100.31% and 99.84-100.55% respectively. The LOD for Sofosbuvir and Ledipasvir were found to be 0.395μg/ml and 0.132μg/ml respectively. LOQ for Sofosbuvir and Ledipasvir were found to be 1.197μg/ml and 0.401μg/ml respectively. Force degradation study also done and method is stability indicating. Developed methods were found to be accurate, precise, rapid and stability indicating for simultaneous estimation of Sofosbuvir and Ledipasvir.Keywords: RP-HPLC, Sofosbuvir, Ledipasvir, ACN, TFA.